2019
DOI: 10.1016/j.celrep.2019.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Surveillance of the Brain by Microglia via cAMP-Regulated Filopodia

Abstract: Article Nanoscale Surveillance of the Brain by Microglia via cAMP-Regulated Filopodia Graphical Abstract Highlights d Microglia use actin-dependent filopodia to efficiently sample the brain parenchyma d Intracellular cAMP drives filopodia growth but induces large process retraction d Norepinephrine and nitric oxide contribute to cAMP-driven filopodia extension d Fine filopodia and large processes establish dual-scale surveillance by microglia This is an open access article under the CC BY-NC-ND license (http:/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
157
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(177 citation statements)
references
References 85 publications
(123 reference statements)
8
157
0
1
Order By: Relevance
“…Intriguingly, many of the RNAs that are altered related to cyclic-AMP signaling, and inhibiting cAMPmediated signaling in microglia with Gi/o coupled DREADD activation exacerbated the acute behavioral signs of withdrawal. We also observed changes in microglia process branching and termination following opioid tolerance that was rapidly reversed during withdrawal and was consistent with cAMP effects on microglia morphology 25 . Together, this data suggests that microglia are actively involved in both opioid tolerance and withdrawal in a compensatory manner.…”
Section: Opioid Abuse Has Reached Epidemic Proportions In the Unitedsupporting
confidence: 82%
See 1 more Smart Citation
“…Intriguingly, many of the RNAs that are altered related to cyclic-AMP signaling, and inhibiting cAMPmediated signaling in microglia with Gi/o coupled DREADD activation exacerbated the acute behavioral signs of withdrawal. We also observed changes in microglia process branching and termination following opioid tolerance that was rapidly reversed during withdrawal and was consistent with cAMP effects on microglia morphology 25 . Together, this data suggests that microglia are actively involved in both opioid tolerance and withdrawal in a compensatory manner.…”
Section: Opioid Abuse Has Reached Epidemic Proportions In the Unitedsupporting
confidence: 82%
“…The microglia imaged in this report do not appear to be classically activated, but rather show modest changes in morphology and process branching and termination. While we did not predict these results, they are entirely consistent with a recent report showing that microglia engage in nanoscale surveillance of the brain via cAMP regulated filopodia 25 . That report showed that decreasing intracellular cAMP results in microglial process elongation, while increasing cAMP causes process retraction.…”
Section: Striatal Microglia Morphology Is Altered By Morphine Toleransupporting
confidence: 80%
“…This increase may reflect more trafficking to the membrane of P2Y 12 receptors in the P2Y 13 KO, better coupling of P2Y 12 to THIK‐1 in the absence of P2Y 13 , or alternatively an effect of the increase of intracellular cyclic AMP level (e.g., altering phosphorylation and potentiating P2Y 12 action) expected when the G i ‐coupled P2Y 13 is knocked out (assuming that there is constitutive activity of P2Y 13 , which is not known). This is in line with our data showing that an elevation of cAMP levels, either by applying forskolin to WT slices or perfusing cAMP intracellularly via the patch‐clamp solution, causes WT microglial cells to adopt features seen in P2Y 13 KO microglia, such as reduced surveillance and ramification (consistent with Bernier et al, ), and a larger P2Y 12 ‐activated THIK‐1 current (Figure S2b). Despite this increased sensitivity to ADP, the P2Y 13 KO cells moved their processes at a similar speed to those of the WT towards an ADP source, where they nevertheless arrived later because the KO cells are less ramified and have shorter processes, and thus they have to grow further than the WT cell processes until they reach their target.…”
Section: Discussionsupporting
confidence: 92%
“…P2RY12 is a nucleotide sensing metabotropic GPCR in the P2Y family of GPCRs that has an important role in the microglial "sensome" (Hickman et al, 2013). P2RY12 regulates the microglial response to tissue damage and the adoption of the amoeboid "activated" microglial morphology (Bernier et al, 2019;Haynes et al, 2006). We found that P2ry12-CreER, unlike the commonly used Cx3cr1-CreER, specifically labeled brain microglia, but not perivascular or meningeal macrophages.…”
Section: Cx3cr1-creermentioning
confidence: 81%